2016
DOI: 10.18632/oncotarget.12393
|View full text |Cite
|
Sign up to set email alerts
|

The andean anticancer herbal product BIRM causes destabilization of androgen receptor and induces caspase-8 mediated-apoptosis in prostate cancer

Abstract: BIRM is an anticancer herbal formulation from Ecuador. Previous study established its antitumor and antimetastatic activity against prostate cancer models. The activity of BIRM against human prostate cancer (PCa) cells was investigated to uncover its mechanism of antitumor activity. In androgen receptor (AR)-expressing PCa cells BIRM was 2.5-fold (250%) more cytotoxic in presence of androgen (DHT) compared to cells grown in the absence of DHT. In AR-positive cells (LAPC-4 and LNCaP) BIRM caused a dose and time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…A potent derivate, DIM (3, 3′‐diindolylmethane) from indole‐3‐carbitol (I3C) have been shown to downregulate AR and AKT signaling which resulted in inhibition of growth in both cell culture and animal models . Similarly, a herbal formulation from Ecuador, BIRM effectively suppressed AR signaling in AR + (LAPC‐4 and LNCaP) cell lines and orthotopic models of CaP . Studies suggested that curcumin analogs suppress DHT‐induced AR activation in AR + CaP cells …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potent derivate, DIM (3, 3′‐diindolylmethane) from indole‐3‐carbitol (I3C) have been shown to downregulate AR and AKT signaling which resulted in inhibition of growth in both cell culture and animal models . Similarly, a herbal formulation from Ecuador, BIRM effectively suppressed AR signaling in AR + (LAPC‐4 and LNCaP) cell lines and orthotopic models of CaP . Studies suggested that curcumin analogs suppress DHT‐induced AR activation in AR + CaP cells …”
Section: Discussionmentioning
confidence: 99%
“…29 Similarly, a herbal formulation from Ecuador, BIRM effectively suppressed AR signaling in AR + (LAPC-4 and LNCaP) cell lines and orthotopic models of CaP. 30 Studies suggested that curcumin analogs suppress DHT-induced AR activation in AR + CaP cells. 31 UroA has been shown to be effective against various carcinomas, and mechanistic studies have reported two primary mechanisms: cell cycle arrest and induction of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effects of KGB on BPH seem very interesting, since this disease is largely characterized by an imbalance between the proliferation and apoptosis [4, 7, 8, 11]. Furthermore, it was recently shown that KGB underground parts were able to abrogate the androgen signaling in prostate malignant cell lineages, besides inducing the apoptosis via caspase 8 activation, thus reinforcing the therapeutic potential of KGB in prostatic diseases [39].…”
Section: Resultsmentioning
confidence: 99%
“…Methanolic extract of Kalanchoe gastonis-bonnieri roots contains uronic acid. The induction of caspase-8-mediated apoptosis was observed in DU145, LNCaP, and PC-3 cells exposed to this extract results in [22]. Evasion of apoptosis is one of the classic features of cancer cells.…”
Section: Effects Of Extracts From Specific Plant Families On Human Prmentioning
confidence: 93%